The diagnostic and prognostic utility of the dual-task tandem gait test for pediatric concussion - Katie A. Van Deventer; Corrine N. Seehusen; Gregory A. Walker; Julie C. Wilson; David R. Howell (Elsevier, 2021)
Background: The tandem gait test has gained interest recently for assessment of concussion recovery. The purpose of our study was to determine the prognostic and diagnostic use of the single- and dual-task tandem gait test, alongside other clinical measures, within 10 days of pediatric concussion. Methods: We assessed 126 patients post-concussion (6.3 ± 2.3 days post-injury, mean ± SD) at a pediatric sports medicine clinic and compared them to 58 healthy controls (age: 15.6 ± 1.3 years; 43% female). We also compared the 31 patients with concussion who developed persistent post-concussion symptoms (PPCS) (age = 14.9 ± 2.0 years; 48% female) to the 81 patients with concussion who did not develop PPCS following the initial assessment (age: 14.1 ± 3.0 years; 41% female). All subjects completed a test battery, and concussion patients were monitored until they experienced concussion-symptom resolution. The test battery included tandem gait (single-task, dual-task (performing tandem gait while concurrently completing a cognitive test) conditions), modified Balance Error Scoring System (mBESS), and concussion symptom assessment (Health and Behavior Inventory). We defined PPCS as symptom resolution time > 28 days post-concussion for the concussion group. Measurement outcomes included tandem gait time (single- and dual-task), dual-task cognitive accuracy, mBESS errors (single/double/tandem stances), and symptom severity. Results: The concussion group completed the single-task (mean difference = 9.1 s, 95% confidential interval (95%CI): 6.1-12.1) and dual-task (mean difference = 12.7 s, 95%CI: 8.7-16.8) tandem gait test more slowly than the control group. Compared to those who recovered within 28 days of concussion, the PPCS group had slower dual-task tandem gait test times (mean difference = 7.9 s, 95%CI: 2.0-13.9), made more tandem-stance mBESS errors (mean difference = 1.3 errors, 95%CI: 0.2-2.3), and reported more severe symptoms (mean difference = 26.6 Health and Behavior Inventory rating, 95%CI: 21.1-32.6). Conclusion: Worse dual-task tandem gait test time and mBESS tandem stance performance predicted PPCS in pediatric patients evaluated within 10 days of concussion. Tandem gait assessments may provide valuable information augmenting common clinical practices for concussion management.